Awardee Goes to School: Upaya Peningkatan Motivasi Siswa untuk Melanjutkan Studi di Pendidikan Tinggi - Fadli Agus Triansyah; Sandi Jembar Wijaya; Nurhuda Teapon; Rini Melani; Erna Dwi Jayanti (Pusat Riset dan Inovasi Nasional, 2023)
Higher education is a stage of education that is believed to be very important in one's life. After completing secondary education, many students feel confused and don't know what to do next. However, continuing education to a higher level is a very wise choice and can open up many opportunities in the future. The purpose of this service and social service is to motivate class XII students at SMA AL-Falah Bandung to continue their studies at tertiary institutions. There are several steps in overcoming the problems faced by students, such as field observations, preparing activity plans, making activity materials, and implementing community service activities. The benefit of this dedication is that it can increase motivation, knowledge, entrance tests and scholarships so as to encourage students' desire to continue their studies at tertiary institutions. This service is carried out by providing education and motivation for activities such as education on LPDP scholarships, Featured scholarships, KIP scholarships, and Games. Based on some of the activities carried out, it is hoped that some changes will occur to students such as increasing the motivation of class XII students to continue their education to tertiary institutions, increasing the knowledge of class XII students about LPDP scholarships, increasing the knowledge of class XII students about KIP scholarships and increasing the knowledge of class XII students. class XII students on superior scholarships (BU).